Capacitance of p‐ and n‐Doped Graphenes is Dominated by Structural Defects Regardless of the Dopant Type. Issue 4 (3rd March 2014) - Ambrosi, Adriano; Poh, Hwee Ling; Wang, Lu; Sofer, Zdenek; Pumera, Martin
Abstract Graphene materials possess attractive properties that can be used for the fabrication of supercapacitors with enhanced energy‐storage performance. It has been shown that both boron and nitrogen doping of graphene can improve the intrinsic capacitance of the material relative to the undoped precursor. We address the question of whether p‐doping (using boron as dopant) or n‐doping (using nitrogen as dopant) leads to increased capacitance relative to undoped graphene materials. Using thermal exfoliation we synthesized both boron‐ and nitrogen‐doped graphene materials and measured capacitance relative to the undoped material. After a full characterization by SEM analysis, X‐ray photoelectron spectroscopy, Raman spectroscopy, gamma‐ray activation analysis, Brunauer–Emmett–Teller analysis, and electrochemical techniques we demonstrate that the doping process does not lead to enhancement of capacitive behavior and that the main characteristic influencing capacitance is the presence of structural defects within the graphitic structure, independent of doping level.